Expressão heteróloga e análise in silico da nova enzima halogenase “LavH” de Streptomyces lavendulae subsp. lavendulae - Teso, João Pedro Nardachione (Universidade Federal de São Carlos, 2026)
Halogenases are enzymes capable of adding a halogen atom to an organic molecule. They are present in diverse genera of microorganisms and exhibit a wide variety of substrates and mechanisms of action, such as flavin-dependent halogenases (FDHs), which are capable of halogenating L-tryptophan using FADH2 (reduced flavin adenine dinucleotide) as a cofactor. There is industrial interest in prospecting for new halogenases, since industrial halogenation methods rely on toxic reagents, lack stereochemical specificity, and generate polluting and harmful byproducts. In this context, the present study reports, for the first time, the heterologous expression and in silico studies of the FDH from Streptomyces lavendulae subsp. lavendulae, herein named LavH. Its activity as an L-tryptophan halogenase with chlorine and bromine was confirmed in vivo in Escherichia coli cells through mass spectrometry, and excellent solubility was observed, unlike other halogenases, which are usually poorly soluble. Furthermore, to increase its viability for use in a biofactory, the enzyme was fused with the E. coli flavin reductase Fre, resulting in a highly insoluble fused enzyme, a finding that contrasts with existing literature. Thus, for in vitro assays, LavH and Fre were purified by affinity chromatography using Ni-NTA (nickel-nitrilotriacetic acid) columns. However, insufficient halogenated product was formed through the in vitro assay for quantification via HPLC, indicating that further assays with longer reaction times are required. For the in silico analyses, sequence alignment and the construction of a phylogenetic tree with other characterized FDHs were performed, revealing an evolutionary proximity to the enzymes BorH and ThaL. Subsequently, the three-dimensional structure of LavH was modeled using AlphaFold3, and molecular docking studies were carried out to elucidate the catalytic site structure and its halogenation preference for the L-tryptophan substrate. Ultimately, this study contributes to the understanding of the activity of this novel halogenase, its structure, and its evolutionary relationship with other enzymes, as well as its potential as an industrial enzyme and the challenges associated with this application.
Heterologous expression and In silico analysis of the novel halogenase "LavH" from Streptomyces lavendulae subsp. lavendulae
Keywords: Halogenase; Biofábrica; Docking molecular; Filogenia; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis